Implications of Oil Price Shocks for the Macroeconomy of African Oil exporting countries : evidence from Angola and Nigeria - Vaz, Carlos Deosvaldo Fragoso (2019)
Angola and Nigeria are the two largest oil production countries in Africa. Oil related activities represent a large proportion of their economic activity which make them vulnerable to oil price shocks. A large body of research suggests that oil price fluctuations have considerable consequences on economic activity, however, the empirical literature on macroeconomics effects of oil price shocks is biased towards developed oil importing countries and lacks developing countries study cases (Bangara & Dunne, 2018). Following existing literature (Jiménez-Rodríguez & Sánchez, 2004), a quarterly four variables SVAR from 2002Q1 to 2017Q4 is applied to investigate the implications of oil price shocks in the key macroeconomic variables of Angola and Nigeria. The study finds that even though the two countries share similar dependence on oil exports, there is strong evidence that they react differently to crude oil price shocks. While in Angola oil prices granger-cause real GDP, real exchange rate and inflation, in Nigeria it only granger-cause real exchange rate. Furthermore, whereas in Angola, a positive oil price shock, increases real GDP, contributes to an appreciation of the real exchange rate and a reduction in inflation. In Nigeria, real GDP doesn’t seem to respond significantly to oil price shocks and at least in the short run neither inflation. These results suggest that Angola is more vulnerable to oil price shocks than Nigeria which maybe explained by the different structure of their domestic economies as well as the differences in the reserve buffers strategies to soften the magnitude of the external shock’s impact.